Scalable structure of coherent polarization beam combining based on tapered diode laser amplifiers. (December 2020) - Zhu, Hongbo; Duan, Xiaoming; Fan, Shengli; Wu, Hao; Lin, Xingchen; Ning, Yongqiang; Wang, Lijun
Highlights: A scalable multi-stage coherent polarization beam combining is introduced. Four amplifiers are coherent polarization beam combined using this novel method. An output of 6.9 W is obtained, and brightness is obtained by a factor of 3.3. Abstract: We develop a scalable multi-stage beam combining system based on the superposition of four tapered diode laser amplifiers using the coherent polarization beam combining. By employing the combination of master oscillator power amplification and active phase control of each amplifier, a stable output power of 6.9 W is obtained with a nearly diffraction-limited beam quality. The combining efficiency is 72%, and the brightness is improved by a factor of 3.3 compared to that of a single amplifier. Our system provides a new solution to obtain a high-coherence and high-brightness diode laser beam.